Anti-adherence effect of coffea liberica ('Barako' Coffee) on streptococcus mutans on enamel - Agustin, Elleen Myre Z.
Coffee is a very common beverage which has been found to have many health benefits. There were studies proving its ability to inhibit the adhesion of Streptococcus mutans on teeth. This anti-caries property was tested in other coffee varieties; however, there were no literature published using Coffea liberica, which is a well-known indigenous crop in the Philippines. For this reason, this study aims to investigate its anti-adherence effect on Streptococcus mutans on enamel. Methodology: Twenty enamel specimens were randomly allocated into four different treatment procedures using green, light, medium and dark roasted Coffea liberica. These groups were immersed in solutions with Streptococcus mutans and were incubated. Growth of S. mutans on these enamel specimens was measured through determination of their optical density with light spectroscopy in order to determine its anti-adherence effect against Streptococcus mutans. The data were analyzed using one-way analysis variance using the Least Significance Different Test with the power of 0.99. Results: All the groups of coffee solutions showed significant difference with the control. The green coffee exhibited 18% reduced adherence, Light roasted coffee had 27% reduced adherence while the dark roasted has 19% reduced adherence. The medium roasted coffee showed the greatest reduced adherence of S. mutans at 28%. Conclusion: Coffea liberica, especially the medium roasted reduced significantly the adherence of Streptococcus mutans on enamel in relation to negative control.